Use of Oxygen-Enriched Oil Dressings in Wound Management: A Scoping Review - Sara Sandroni; Valerio Della Bella; Alessandro Sili; Jacopo Fiorini (Journal of Clinical Medicine, 2026)
Background/Objectives: Oxygen-enriched oils represent an emerging class of advanced dressings based on the controlled release of reactive oxygen species, with the potential to modulate the wound microenvironment and support reparative processes. Despite their increasing clinical use, the available evidence remains fragmented, and no comprehensive synthesis is currently available on their fields of application and associated outcomes. Methods: A scoping review was conducted in accordance with the Joanna Briggs Institute methodology and the PRISMA-ScR reporting guidelines. PubMed, CINAHL, Scopus, and Web of Science were searched without time restrictions. Studies conducted in patients and evaluating oxygen-enriched oil-based dressings for the management of skin wounds were included. Two independent reviewers selected the studies, extracted and narratively synthesized the data, and performed the quality appraisal. Results: The search identified 142 records; after the selection process, nine studies including a total of 501 patients were included. The studies comprised different designs, ranging from randomized controlled trials to case reports. Applications included pediatric postoperative wounds (distal hypospadias and pilonidal disease), postsurgical wounds related to hidradenitis suppurativa, angular cheilitis, and oncological wounds. The most frequently investigated outcomes included reductions in healing time, pain, local complications, and infectious burden, as well as improvements in scar quality and patient satisfaction. Conclusions: Oxygen-enriched oils represent a promising wound-care strategy in different clinical settings. Although preliminary findings are favorable, independent controlled studies with larger samples and standardized outcomes are needed to define their comparative effectiveness and role in clinical practice more precisely.